The effect of delayed cord clamping on blood sugar levels on 34–36 week neonates exposed to late preterm antenatal steroids. (17th September 2022) - Hitchings, Laura; Rodriguez, Marcella; Persaud, Reva; Gomez, Luis
Abstract: Objective: Neonatal hypoglycemia is a known side effect of antenatal betamethasone (BMZ) given for fetal maturation. We sought to investigate if delayed cord clamping (DCC) has an impact on neonatal hypoglycemia induced by antenatal late preterm BMZ administration. Material and methods: Retrospective cohort study (January 2019–May 2019) of pregnancies undergoing delivery at 34–0/7 to 36–6/7 weeks at a single center included in two groups: DCC + BMZ and BMZ-only (no DCC). The primary outcome was the occurrence of neonatal hypoglycemia at the first hour after delivery. Results: A total of 62/188, 32.98% (DCC + BMZ group) and 45/100, 45% (DCC-only group) infants presented with hypoglycemia at 1-h after birth (adjusted p  = .06; OR 0.73, 95% CI 0.54–1.01). When stratified according to gestational age at delivery, DCC was associated with a 46% reduction in the occurrence of neonatal hypoglycemia among those born at 35–0/7 to 35–6/7 weeks (adjusted p  = .033; OR 0.54, 95% CI 0.33–0.88) and 35% reduction among those born at 36–0/7 to 36–67 weeks (adjusted p  = .046; OR 0.65, 95% CI 0.43–0.97). Conclusion: In our cohort, delayed cord clamping in infants receiving late preterm BMZ born between 35–0/7 and 36–6/7 weeks' gestation protects from early neonatal hypoglycemia.